Providers of and participants in suicide assistance in Germany: A field description based on expert interviews - Sven Schwabe; Franziska A. Herbst (PLoS ONE, 2026)
Background Over the past 20 years, assisted dying practices have been legalised in an increasing number of countries around the world. After a decision of the German Federal Constitutional Court in 2020, suicide assistance is unregulated in Germany but official data about the implementation of suicide assistance is lacking. Aim This study aims to explore the providers of and participants in suicide assistance in Germany. Methods 16 semi-structured qualitative expert interviews were conducted with scientists, officials, journalists and members of right-to-die organisations between May and July 2025. Experts were chosen due to their extensive theoretical and practical knowledge of the practice of assisted suicide in Germany. The interviews were digitally recorded, transcribed verbatim and analysed using qualitative content analysis, according to Mayring. Results A total of five main providers and participants involved in the practice of assisted suicide in Germany were identified: 1) right-to-die organisations, 2) medical and non-medical suicide assistants, 3) treating physicians, 4) funeral directors and 5) relatives and friends. Right-to-die organisations and suicide assistants from various professions regularly provide suicide assistance and carry out all relevant tasks, including the provision of information, organisation, implementation and documentation. Treating physicians, funeral directors, relatives and friends may be asked to provide suicide assistance in individual cases and take on specific tasks. Other healthcare professionals (e.g., nurses, pharmacists) and professional groups (e.g., police officers, prosecutors) may also be confronted with suicide assistance and become involved in the process. Discussion Given the minimal regulation of assisted suicide in Germany, the landscape of providers and supporters appears to be diversifying and growing increasingly complex. Future research should examine the roles, experiences, challenges and best practices of the various actors involved in the provision of assisted suicide. Trial registration The study was prospectively registered in the German Clinical Trials Register (Deutsches Register Klinischer Studien) under Registration N° DRKS00034574, on 04 July 2024. It is also searchable via the International Clinical Trials Registry Platform Search Portal of the World Health Organization, under the same registration number.